Developing agentic learners for 21st Century practice: a pedagogic approach in Occupational Therapy - Lee, Hoe; Flavell, Helen; Parsons, Dave; Parsons, Richard; Falkmer, Torbjorn (Association of Schools of Allied Health Professions, 2015)
In this paper an approach to teaching Occupational Therapy students how to create orthoses, whilst at the same time developing higher order critical thinking, reflective and clinical reasoning skills, is described. The scaffolded nature of the learning activities, incorporating Kolb's reflective learning cycle, was used to support students' capacity for clinical reasoning and better prepare them for clinical placement. The peer assessment element was also designed to support the experiential learning by allowing students to test their evaluation of hand orthoses, compare their assessment with an expert’s, and identify areas for improvement. Students who demonstrated higher grades for the written reflection assessment showed better agreement with the experts (smaller bias, p<0.01). This study concluded there was a correlation between students' capacity for reflective thinking and the development of clinical reasoning. Furthermore, the reflective writing exercise encouraged students to generalise their skills beyond the classroom. The approach and findings of this study are relevant to a range of allied health professions through providing a process to support the development of higher order critical thinking, reflection and reasoning skills. Furthermore, the study provides an evidence-base to demonstrate that higher reflective skill capacity and critical thinking is crucial to creating agentic learners.